2021
DOI: 10.1200/jco.2020.39.28_suppl.300
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker testing patterns in patients with stage IV non-small cell lung cancer (NSCLC) in U.S. community-based oncology practice setting.

Abstract: 300 Background: This study evaluated rates of biomarker testing for patients with stage IV non-squamous NSCLC, which is known to have a ̃40% biomarker-positive rate (AMP, 2020), in a community-based oncology practice setting in the United States (US). Methods: A retrospective study was performed using data from a US electronic medical record database of patients aged ≥18 years with an initial diagnosis (index dx) of stage IV non-squamous NSCLC between Jan 1, 2015 and Dec 31, 2019. Unstructured data on molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 22 Another single community-based practice study found that 59% of patients received NGS-based testing. 15 Although the findings from this study suggest that NGS-based testing may be higher among the clinical practices in the Flatiron Health network, it is clear that underutilization of recommended testing is a national problem.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“… 22 Another single community-based practice study found that 59% of patients received NGS-based testing. 15 Although the findings from this study suggest that NGS-based testing may be higher among the clinical practices in the Flatiron Health network, it is clear that underutilization of recommended testing is a national problem.…”
Section: Discussionmentioning
confidence: 62%
“… 11 , 12 , 13 There is emerging work that has begun to explore diagnostic testing in real-world settings, but gaps remain in the knowledge of current practices in biomarker testing and its utilization across community and academic practice settings. 5 , 14 , 15 This study, therefore, was designed to evaluate the utilization of single-gene and panel-based biomarker testing (by NGS) among patients with nonsquamous advanced or metastatic NSCLC in community and academic practice settings across the United States to quantify the rates of testing in current practice to inform the development of guidelines or initiatives to address gaps in the receipt of biomarker testing.…”
Section: Introductionmentioning
confidence: 99%
“…18,24 Despite recommendations that biomarker testing be conducted to guide first-line treatment selection, many patients do not have broad molecular testing performed on their tumor tissue as reported in multiple studies. [25][26][27][28][29] Data from the MYLUNG study reported changes in rates of molecular testing from April 2018 to March 2020 for genes including EGFR (71%!71%), BRAF (51%!59%), ROS1 (69%!67%), and ALK (71%!70%), and reported an overall increase of 33% to 45% in the use of next-generation sequencing (NGS)-based testing in patients with a/mNSCLC. 28 In another study, despite a reported increase in the use of NGS-based testing from 28% (2015) to 68% (2020) in patients with a/mNSCLC in the United States, approximately 33% of patients did not receive testing for all guidelinerecommended biomarkers.…”
Section: Introductionmentioning
confidence: 99%